Is quantification of lymphovascular space invasion useful in stage 1B2 cervical carcinomas?. (May 2015) - Scurry, J.; Hacker, N. F.; Barlow, E.; Friedlander, M.; Jackson, M.
Abstract: The objective was to determine whether quantification of lymphovascular space invasion (LVSI) by simple techniques adds prognostic information above its mere identification in stage 1B2 cervical cancer. The method was to quantify LVSI by extent, density and distance from the advancing front in 88 consecutive stage 1B2 cervical cancers treated by radical hysterectomy and pelvic lymphadenectomy and to compare them with pelvic lymph node status and local and distant recurrence. The results were that LVSI involved more tumour blocks, was denser and extended a further distance in those with positive nodes. However, effective adjuvant therapy confounded the association between quantification of LVSI and local recurrence. Furthermore, pelvic lymph node status was a stronger predictor of distant recurrence than any degree of LVSI. In conclusion, quantifying LVSI in stage 1B2 cervical cancer is a good predictor of lymph node metastasis, but is not useful where the lymph node status is known.